ЎҚУВЧИЛАРДА МУСИҚИЙ-БАДИИЙ ДИДНИ ШАКЛЛАНТИРИШНИНГ ПЕДАГОГИК МЕЗОНЛАРИ (ART AND CULTURE BULLETIN, 2023)
The article outlines the criteria for the formation of musical taste of pedogogs in musicalschools. Basically, it is said about the extent to which the formation of musical taste has reached us fromhistory to us the criteria for which it is currently developed and embodied.
Keywords: pedogogy; music; music schools; musical taste; classroom; independent education; music and art ethics; music ethics.